Hyperchromatic structural color for perceptually enhanced sensing by the naked eye - Talukdar, Tahmid H. (Proc Natl Acad Sci U S A, 2020)
Colorimetric sensors offer the prospect for on-demand sensing diagnostics in simple and low-cost form factors, enabling rapid spatiotemporal inspection by digital cameras or the naked eye. However, realizing strong dynamic color variations in response to small changes in sample properties has remained a considerable challenge, which is often pursued through the use of highly responsive materials under broadband illumination. In this work, we demonstrate a general colorimetric sensing technique that overcomes the performance limitations of existing chromatic and luminance-based sensing techniques. Our approach combines structural color optical filters as sensing elements alongside a multichromatic laser illuminant. We experimentally demonstrate our approach in the context of label-free biosensing and achieve ultrasensitive and perceptually enhanced chromatic color changes in response to refractive index changes and small molecule surface attachment. Using structurally enabled chromaticity variations, the human eye is able to resolve ∼0.1-nm spectral shifts with low-quality factor (e.g., Q ∼ 15) structural filters. This enables spatially resolved biosensing in large area (approximately centimeters squared) lithography-free sensing films with a naked eye limit of detection of ∼3 pg/mm(2), lower than industry standard sensors based on surface plasmon resonance that require spectral or angular interrogation. This work highlights the key roles played by both the choice of illuminant and design of structural color filter, and it offers a promising pathway for colorimetric devices to meet the strong demand for high-performance, rapid, and portable (or point-of-care) diagnostic sensors in applications spanning from biomedicine to environmental/structural monitoring.